Andragogy for Music Therapy Education and Training: Four Conceptualizations to Help Students Thrive in and Outside the Classroom - Jang, Sekyung (Voices: A World Forum for Music Therapy, 2024)
The transdisciplinary as well as practical nature of music therapy profession makes it challenging for music therapy educators to design courses and curricula that prepare students to integrate theory and practice, balance the art and science of music therapy, and become independent learners. Existing literature on educational approaches focuses on specific areas such as clinical musicianship and research skills and does not provide holistic views or conceptualizations through which educators can design courses and curricula. In this paper, four conceptualizations and teaching strategies that may aid current educational practices are explored: building a culture of learning, life-long learning, self-directed learning, and teaching diversity and multicultural contexts. Educators’ roles are also provided in cultivating learning environments where students feel safe to explore new ideas and music therapy methods, develop cognitive and social skills as life-long learners, utilize internal motivation to learn and grow with autonomy, and cultivate self-awareness in order to approach clients with cultural humility and knowledge.